Memantine as a neuroprotective agent in ischemic stroke: Preclinical and clinical analysis - Pichardo-Rojas, Diego; Pichardo-Rojas, Pavel Salvador; Cornejo-Bravo, José Manuel; Serrano-Medina, Aracely (Frontiers in Neuroscience, 2023)
The primary mechanism for neuron death after an ischemic stroke is excitotoxic injury. Excessive depolarization leads to NMDA-mediated calcium entry to the neuron and, subsequently, cellular death. Therefore, the inhibition of the NMDA channel has been proposed as a neuroprotective measure in ischemic stroke. The high morbimortality associated with stroke warrants new therapies that can improve the functional prognosis of patients. Memantine is a noncompetitive NMDA receptor antagonist which has gained attention as a potential drug for ischemic stroke. Here we analyze the available preclinical and clinical evidence concerning the use of memantine following an ischemic stroke. Preclinical evidence shows inhibition of the excitotoxic cascade, as well as improved outcomes in terms of motor and sensory function with the use of memantine. The available clinical trials of high-dose memantine in patients poststroke have found that it can improve patients' NIHSS and Barthel index and help patients with poststroke aphasia and intracranial hemorrhage. These results suggest that memantine has a clinically relevant neuroprotective effect; however, small sample sizes and other study shortcomings limit the impact of these findings. Even so, current studies show promising results that should serve as a basis to promote future research to conclusively determine if memantine does improve the outcomes of patients’ post-ischemic stroke. We anticipate that future trials will fill current gaps in knowledge, and these latter results will broaden the therapeutic arsenal for clinicians looking to improve the prognosis of patients poststroke.